'Here's the iPad'. The BTEC philosophy: how not to teach science to vocational students. Issue 4 (1st October 2016) - Hobley, Janet
Abstract: This research examines the delivery of scientific knowledge in vocational BTEC courses in terms of the concept of vocational pedagogy. It draws on empirical data from observations of teaching, semi-structured interviews and a documentary analysis of syllabuses from both A level and BTEC examining boards. Theoretical concepts of pedagogical knowledge as well as more recent concepts of how technology influences pedagogical techniques are used to investigate the way that technology is used in the teaching of scientific concepts in these vocational contexts. The initial hypothesis drawn was that the Further Education Learning Technology Advisory Group (FELTAG) established in 2013 was creating 'shallow learning' through the ineffective use of technology. As a result there was emerging a 'BTEC philosophy' of teaching science to vocational learners using learning technology (LT) as a 'quick fix' approach. However as the research progressed it became clear that one of the colleges involved had embraced the pedagogical uses of LT in an innovative way and that what was really lacking were strong 'bodies of knowledge' within the curriculum of vocational courses that had science within the curriculum.